Implementation research to evaluate an educational intervention for people who inject drugs. (13th November 2019) - Roux, P; Magen, C; Stranz, R; Schatz, E; Verdes, L; Curado, A; Tsiakou, T; Roy, E; Carrieri, P
Abstract: Objective: In the context of disseminating harm reduction (HR) programmes in Europe, the Eurosider project aims to study the transferability of an effective educational intervention for people who inject drugs (PWID) to four European countries (Bulgaria, Greece, Portugal and Romania). This intervention, entitled Individually-Tailored Support and Education for Safer Injection (ITSESI), has been shown to reduce HIV-Hepatitis C Virus (HCV) risk practices by offering educational supervision during all phases of the injection sequence, from pre- to post-injection. Methods: The project employs mixed methods and implementation science. The exploratory first step used qualitative interviews and other available data in each country. The second step consists in implementing and evaluating the intervention using a 6-month study conducted among 300 PWID enrolled in the 4 countries. They are interviewed at baseline and at 6 months. The third step will consist in designing, promoting and disseminating all the tools necessary to transfer ITSESI at the European level. Results: Results from the exploratory phase highlighted two main determining factors for the feasibility of implementing ITSESI: funding and a repressive legal context. Preliminary results from a quantitative analysis of data from the second step will provide a baseline description of the 300 PWID. Discussion: Findings to date indicate that an exploratory phase is crucial to adapt and transfer the intervention to local contexts and to evaluate it. More globally, the Eurosider project will 1) help understand each local context to adapt the intervention accordingly; 2) assess the feasibility and effectiveness of ITSESI in different contexts; 3) promote and disseminate tools and training to implement the intervention at the European level. Key messages: People who inject drugs in European countries report HIV-HCV risk practices and adequate prevention should be provided. The implementation of an innovative educational intervention for people who inject drugs may be one response but requires to take into account contextual factors: funding and repressive drug policy.